ЕЛЕКТРОМАГНІТНІ ВІБРОЗБУДЖУЮЧІ СИЛИ ТУРБОГЕНЕРАТОРА В МАНЕВРЕНИХ РЕЖИМАХ РОБОТИ - Васьковський, Ю.М.; Мельник, А.М. (Інститут електродинаміки НАН України, Київ, 2016)
The paper considers laws of change of electromagnetic vibration disturbing forces of a turbogenerator (ТG) of its active and reactive power in maneuverable operating conditions. Study for ТG type ТGV-200-2 by power 200 MW have been spent. The generated a mathematical model of electromagnetic field allows to simulate of signals of vibration sensor as time functions. The model allows to define optimal performance of ТG with the least of vibration level. The analysis of V-curve for three values of power of ТG is carried out. It is shown that in an overexcitated vibration disturbin forces insignificantly depend on of power of ТG. In an underexcitated is inexpedient to reduce essentially the active load. Since, significant increase of vibration on (35... 45)% is observed. In a condition of the synchronous compensator without active load the greatest of vibration level of ТG is observed. References 12, table 1, figures 7.